Strategi Pelaksanaan PI Pada Mahasiswa PKK UST Melalui Analisis SWOT - Endang Wani Karyaningsih; Anggri Sekar Sari (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2019)
The Home Economic Education department is a vocational study program with 70% of available courses in the form of eyes. One of the practical courses that must be taken is industrial practice (IP). IP was held for 160 hours in the industry and continued with reporting. The problem that often arises in the implementation of the IP is that students are hesitant about the choice of industry type, lack of confidence, and inaccurate time in making reports. The purpose of this study is to find the right model or strategy in determining the implementation of IP. The method used to find data in the study is a questionnaire, and data analysis through SWOT. IP evaluation is taken from the field value and report presentation value. The value of the field has a greater portion than the value of the presentation. From a number of industry value documents, it turns out that there are variations in valuations that are given by the industry. This variation of value is of course based on the ability of each student in terms of readiness to join the IP.